The Effect of Scientific Approach on Speaking Competency and Its Relationship to Achievement Motivation - Ni Made Ernila Junipisa (Universitas Pendidikan Ganesha, 2019)
This experimental study aims at investigating the effect of scientific approach and achievement motivation upon speaking competency of ninth graders of SMP Pancasila Canggu in the academic year 2017/2018. This research applied 2x2 factorial design. Sixty students were selected as sample through random sampling. Data of students’ speaking and achievement motivation were collected by using multiple choice tests. The acquired data were analyzed statistically by Two Way Analysis of Variance (Two Way ANOVA) and Tukey test to know the interaction effect at 5% significance level. This research discovered that 1) Scientific Approach affects significantly on students’ speaking competency, 2) there is a significant interaction effect of teaching strategy and achievement motivation on students speaking competency, 3) Scientific Approach affects significantly on the high motivation students’ speaking competency, and 4) Conventional Strategy affects significantly on the low motivation students’ speaking competency.